5.5 GHz film bulk acoustic wave filters using thin film transfer process for WLAN applications - Tingting Yang; Chao Gao; Yaxin Wang; Binghui Lin; Yupeng Zheng; Yan Liu; Cheng Lei; Chengliang Sun; Yao Cai (Microsystems & Nanoengineering)
Abstract Wireless local area network (WLAN) has gained widespread application as a convenient network access method, demanding higher network efficiency, stability, and responsiveness. High-performance filters are crucial components to meet these needs. Film bulk acoustic resonators (FBARs) are ideal for constructing these filters due to their high-quality factor (Q) and low loss. In conventional air-gap type FBAR, aluminum nitride (AlN) is deposited on the sacrificial layer with poor crystallinity. Additionally, FBARs with single-crystal AlN have high internal stress and complicated fabrication process. These limit the development of FBARs to higher frequencies above 5 GHz. This paper presents the design and fabrication of FBARs and filters for WLAN applications, combining the high electromechanical coupling coefficient ( $${K}_{{\rm{t}}}^{2}$$ K t 2 ) of Al0.8Sc0.2N film with the advantages of the thin film transfer process. An AlN seed layer and 280 nm-thick Al0.8Sc0.2N are deposited on a Si substrate via physical vapor deposition (PVD), achieving a full width at half maximum (FWHM) of 2.1°. The ultra-thin film is then transferred to another Si substrate by wafer bonding, flipping, and Si removal. Integrating conventional manufacturing processes, an FBAR with a resonant frequency reaching 5.5 GHz is fabricated, demonstrating a large effective electromechanical coupling coefficient ( $${{k}}_{{\rm{eff}}}^{2}$$ k eff 2 ) of 13.8% and an excellent figure of merit (FOM) of 85. A lattice-type filter based on these FBARs is then developed for the Wi-Fi UNII-2 band, featuring a center frequency of 5.5 GHz and a −3 dB bandwidth of 306 MHz, supporting high data rates and large throughputs in WLAN applications.